2003
DOI: 10.1038/sj.onc.1206712
|View full text |Cite
|
Sign up to set email alerts
|

EGF receptor mediates adhesion-dependent activation of the Rac GTPase: a role for phosphatidylinositol 3-kinase and Vav2

Abstract: Organization of the actin cytoskeleton in eucaryotic cells is controlled by small GTPases of the Rho family. Rac becomes activated by growth factor stimulation and integrin-mediated cell adhesion to extracellular matrix and is known to have a crucial role in lamellipodia formation, cell spreading and migration. At present, the intracellular pathways that connect cell surface receptors to Rac activation are poorly characterized. It has been reported previously that integrin-mediated cell attachment induces acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 34 publications
1
69
0
1
Order By: Relevance
“…Rac1 transduces signals from both the EGFR and PI3K in other cell types (23,24,25), consistent with their contribution to COX-2 expression in papilloma cells (10). Slice et al (25) reported that signaling by small GTPases results in COX-2 expression in 3T3 cells through independent, parallel signaling pathways.…”
Section: Discussionmentioning
confidence: 66%
“…Rac1 transduces signals from both the EGFR and PI3K in other cell types (23,24,25), consistent with their contribution to COX-2 expression in papilloma cells (10). Slice et al (25) reported that signaling by small GTPases results in COX-2 expression in 3T3 cells through independent, parallel signaling pathways.…”
Section: Discussionmentioning
confidence: 66%
“…Blockade of EGF-R or PDGF-R can alter phosphatidylinositol 3Ј-kinase activity, leading to a change in interstitial fluid homeostasis, which results in a reduction of interstitial hypertension with an increase in transcapillary transport (72)(73)(74). The roles of EGF and PDGF in angiogenesis have been reported for several human tumors (75)(76)(77)(78), and destruction of the vasculature within neoplasms can produce necrosis of actively growing tumors (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work of Alan Hall has described the role of Rho GTPases in regulating assembly of focal adhesions in response to growth factors leading to increased cell migration 21. Activated Rho GTPases like RAC1, CDC42, and RHOA through kinases like p‐21 activated kinase (PAK) and PI3K control cell shape by bringing about changes in the actin stress fibers and polymerization of F‐actin through ACTR2/3 complex resulting in cell spreading and migration 22, 23.…”
Section: Introductionmentioning
confidence: 99%